Load-settlement behaviour of model pile groups in sand under vertical load - Sales, Mauricio Martines; Prezzi, Monica; Salgado, Rodrigo; Choi, Yoon Seok; Lee, Jintae (Journal of Civil Engineering and Management, 2017)
Model pile load testing is effective to study the load-settlement behaviour of pile foundations given the controlled environment in which the testing is done. This paper reports a testing program in a large calibration chamber involving individual piles and pile groups installed in sand samples of three different densities. Tests on both nondisplacement and driven piles are evaluated to assess the influence of the pile installation process on pile load-settlement response. A method is proposed to predict the load-settlement response of a pile group based on the response of a single pile. The method is shown to produce estimates that are in good agreement with measurements. The influence of pile group configuration, pile spacing, soil density and method of pile installation is discussed.